The influence of CyberCrime on the level of trust of users of Ewallet products in Mobile Banking Services reviewed Islamic Economic Perspective (user study of UIN RIL student Fund E-Wallet application) - Pramestu, Rilo Abdi; Kurniawan, Muhammad; Kurniawan, Agus (CV. Civiliza Publishing, 2025)
The development of financial technology, especially mobile banking services and e-wallet applications, increasingly provides convenience in digital transactions. However, the increasing incidence of cyber crime (cyber crime) poses serious problems related to user confidence in the security of the service. This study aims to analyze the influence of cyber crime on the level of confidence of e-wallet users in mobile banking services in the perspective of Islamic economics. With quantitative methods and survey approaches to student users of the Dana e-wallet application at UIN RIL, the results of the study show that cyber crime has a positive influence on user trust. The Islamic economic perspective emphasizes the importance of Amanah and adil in maintaining trust so that digital transactions remain halal and reliable. This study recommends improving security, educating users, and implementing sharia principles in e-wallet services.